Đặc điểm phân bố mưa trên lãnh thổ Việt Nam - Thành, Phạm Xuân; Anh, Nguyễn Xuân; Huy, Lê Việt; Quân, Lê Như; Fontaine, Bernard; Philippon, Nathalie (Vietnam Journal of Earth Sciences, 2009)
Spatial and temporal study of rainfall characteristics over Vietnam